2018
DOI: 10.17221/9/2017-pps
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal potential and biochemical effects of monoterpenes and phenylpropenes on plant

Abstract: Marei G.I.Kh., Abdelgalei S.A.M. (2018): Antifungal potential and biochemical effects of monoterpenes and phenylpropenes on plant pathogenic fungi. Plant Protect. Sci., 54: 9-16.To develop new natural fungicides, six monoterpenes and two phenylpropenes were tested for their antifungal activity against eight plant pathogenic fungi. The results of the mycelial growth inhibition assay showed that trans-cinnamaldehyde was the most potent compound against the eight tested fungi with EC 50 values ranging between 0.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…100 μg/mL. 40,41 The present study included two commercial antifungals, that is, mancozeb (a Mn/Zn dithiocarbamate salt) and iprodione (an N -substituted hydantoin carboxamide). The IC 50 values of these antifungals were 0.031 and 0.043 mM, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…100 μg/mL. 40,41 The present study included two commercial antifungals, that is, mancozeb (a Mn/Zn dithiocarbamate salt) and iprodione (an N -substituted hydantoin carboxamide). The IC 50 values of these antifungals were 0.031 and 0.043 mM, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, studies have identified many novel structures with excellent activity to pathogenic microorganisms, such as caffeic acid, 3,4-dicaffeoylquinic acid, 1,5-dicaffeoylquinic acid, trans-cinnamaldehyde, (-)-menthone, benzofurans, crinipellins, and (+)-yahazunol (Figure 2d) (Chen et al, 2013;Gehan & Samir, 2017;Han et al, 2018;Loiseleur, 2017;Ruiz-Vasquez et al, 2018;Sparks et al, 2017;Zhang, Wang, et al, 2018). Zhang, Wang, et al (2018) developed a scalable method for synthesizing (+)-yahazunol and other related meroterpenoids (Figure 2d, bottom part).…”
Section: The Identification Of Activit Y Of Natural Products Is a Key Driver In The Design Of New Chemical Control Productsmentioning
confidence: 99%
“…According to Cavanagh and Wilkinson [2], Bakkali et al [3], and Sienkiewicz et al [1], the effectiveness of oils is determined by the chemical composition (qualitative and quantitative) of the active substance contained in the oil. High biological activity compounds include the following: terpinene, limonene, germacrene, citronellyl acetate, caryophyllene, thymol, carvacrol, eugenol, eucalyptol, terpineol, and linalool [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies showed that EsO exhibit antifungal properties, manifested by inhibition or restriction of mycelium development, inter alia, Fusarium [11][12][13][14]. Fungal growth disorders are caused by changes in the structure of fungi associated with the interaction of EsO on the enzymes responsible for cell wall synthesis.…”
Section: Introductionmentioning
confidence: 99%